Effect of compressed air and cutting speed on surface roughness of 6061 Aluminium Alloy / Nor Aznan Mohd Nor...[et al.] - Mohd Nor, Nor Aznan; Baharudin, B.T.H.T; Arifin, M.K.M; Z., Leman (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
Globally, the manufacturing industry is moving towards sustainable manufacturing in order to preserve natural resources and human well-being. Compressed air is not only recognised as an ideal option to replace cutting fluid in order to flush away chips for surface quality reasons but also to reduce the environmental burden due to disposal of used cutting fluid, as well as to minimise the consumption of natural resources in cutting fluid production. However, chip clearing in order to prevent a tool from recutting the chips is a great challenge in dry milling. Considering this issue, compressed air is necessary to prevent a tool from recutting the chips. In this experimental work, slot milling experiment based on 3² factorial experimental design was conducted in order to identify the effect of compressed air and cutting speed on the surface roughness of 6061 aluminium alloy. Three levels of compressed air and cutting speed were used, whereas the depth of cut and feed rate were held constant. The results demonstrated that the higher amount of compressed air and cutting speed will lead to high surface quality and vice versa. Nevertheless, the surface roughness generated at different cutting speed does not depend on the amount of compressed air.